Titik Temu Pancasila dan Etika Politik Gereja dalam Melawan Radikalisme di Indonesia - David Eko Setiawan; Firman Panjaitan (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
The condition of intolerance that grows and develops in society has resulted in Indonesia being prone to disintegration. The most effective action against this radicalism movement is not done physically but ideologically. The most appropriate ideological tools against this movement are Pancasila and political ethics because both teach about divine and human values. However, both of them still receive less attention and are used in counter-radicalism activities. This study aims to explore the intersection of Pancasila and church political ethics as an antidote to radicalism in Indonesia. This research uses a qualitative approach with the library method. This study indicates that the meeting point between Pancasila and church political ethics lies in the divine value that lives human values. Divine values can only be preserved and developed in human values. It affirms that all forms of oppression and violence that interfere with human values must be rejected and eliminated from the life of the nation and state in Indonesia. Thus, Pancasila and church political ethics in Indonesia can be the most appropriate values to fight radicalism. These findings can make a scientific contribution to increasing the role of the church in living the values of Pancasila to counter radicalism in Indonesia.